The nurse's role in the postoperative period of cardiac surgery: an integrative review of the literature (Research, Society and Development, 2023)
Objective: To identify the scientific evidence about the nursing care provided to patients undergoing cardiac surgery and discuss the role of nurses in this context of care, based on the evidence found. Method: This is an integrative literature review, descriptive and of bibliographic research type, qualitative in nature. The Bardin method was used, with data search carried out through the online platforms of the databases contained in the VHL duly published in journals in the time lapse from 2017 to 2022.Results: In category I:It is evidenced that the surgery imposes constant changes of physical, social and psychological order for that patient and point to positive responses to musical interventions. In category II: The articles mention about acute pain with a higher level of evidence and point out that nursing is in constant concern with technical care at the bedside and that the nursing process contributes to quality care. Conclusion: Advances in cardiac surgical treatment, main diagnoses, goals and nursing interventions were clarified from the moment of screening, treatment and recovery. It is expected that this study will help nurses working in the postoperative period, so that they can base their daily activities with the patients.